2013
DOI: 10.3747/co.20.1364
|View full text |Cite
|
Sign up to set email alerts
|

Are Two-Centimeter Breast Cancers Large or Small?

Abstract: Background: Node-negative breast cancers from 2 cm to 5 cm in size are classified as stage ii, and smaller cancers, as stage i. We sought to determine if the prognosis of women with a breast cancer exactly 2 cm in size more closely resembles that of women with a stage i or a stage ii breast cancer. Methods: Using a cohort of 4265 young women with breast cancer, we compared the 10-year breast cancer mortality rates for women who had a tumour 0.1–1.9 cm, exactly 2.0 cm, and 2.1–2.9 cm. Results: In the first 3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…As a consequence, oncologists can determine the causes of BC appearance considering the knowledge of when the first tumor cell appeared, which can lead to the development of prevention methods. The relationship between the PT and sdMTSs can provide a deeper understanding of the BC process [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 36 , 37 , 38 , 39 , 40 , 41 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. The calculation of the earliest diagnostic period can help with the assignment of early treatment and increase survival [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, oncologists can determine the causes of BC appearance considering the knowledge of when the first tumor cell appeared, which can lead to the development of prevention methods. The relationship between the PT and sdMTSs can provide a deeper understanding of the BC process [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 36 , 37 , 38 , 39 , 40 , 41 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. The calculation of the earliest diagnostic period can help with the assignment of early treatment and increase survival [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that (a) the mortality rate depends directly on the PT size and (b) the risk of sdMTS appearance depends directly on the PT size [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][36][37][38][39][40][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: The Relationship Between the Size Of The Pt And An Appearance Of The Sdmtss And Tvdtmentioning
confidence: 99%
“…Most probably women in the community would have picked up the breast lumps more than 2 cm in size. 9 If detected early, the prognosis of breast cancer is very good and the mortality can be reduced. 10 Another community based study done in Kannur district, Kerala showed 23 cases of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were excluded if there was a minimal delay in their presentation of less than 3 months, which is a time criterion arbitrarily used by many investigators [19][20][21] , or if their tumor size at time of diagnosis was less than 2 cm, since tumors greater than or equal to this size have been associated with significant mortality benefits and more consistent detection by screening mammogram [22,23] . We also excluded participants who had received a mammogram within 1 year of their diagnosis, as they utilized preventative services in accordance with the strictest available guidelines [24,25] and could most clearly be classified as interval cancers, which have been associated with longer mean waiting times to breast cancer diagnosis compared with screen-detected cancers [26] .…”
Section: Study Populationmentioning
confidence: 99%